(3GdadSaI GdfhQGfjI GdbQCfjI (B:s (3YHO GdZRGdj QDjI fbOjI dacQ GdZRGdj h adSaJg (B/s - (3GeGe,RcQjG HTjQ s ((3GdchjJ (B:s (3ecJHI GdadGM ,s, 1989)
(3GdSjQI GdPGJjI ddZRGdj ef eDdaGJ GdZRGdjs
Keywords: (3GdZRGdjs; (3GdadSaIs